(untitled) (Indian Journal of Arid Horticulture, 2025)
Aegle marmelos Correa, commonly known as bael, is one of the most significant medicinal plants of India. It thrives under adverse agro-climatic conditions and can adapt successfully to a wide range of habitats, from arid and semi-arid to mesophytic conditions. It also exhibits a wide temperature tolerance, ranging from 4°C to 48°C. The importance of Aegle marmelos lies in its curative properties, making it one of the most valuable medicinal plants in India.